Correlations between ischaemic cerebral white matter change and the neurocognitive profiles in apparently asymptomatic individuals - Ghazali, Mazira Mohamad (2017)
White matter hyperintensities (WMHs), asymptomatic lacunar infarcts, brain microbleeds (BMBs), and enlarged perivascular spaces (EPVS) have been identified as silent lesions attributable to cerebral small vessel disease (CSVD). All these markers have been individually linked to predisposition of cognitive impairment. This study aimed to examine the relationship between CSVD from incidental MRI findings and neuropsychological performance among apparently healthy individuals. An ethical approval was obtained from the Jawatankuasa Etika Penyelidikan Manusia Universiti Sains Malaysia (JEPeM-USM) [Ref: USM/JEPeM/15030096]. This was a pilot study that involved random selection of subjects‘ population who attended Klinik Rawatan Keluarga, Hospital Universiti Sains Malaysia. The QRISK2, an online-based cardiovascular risk prediction was employed to stratify the cerebrovascular risk for the recruited subjects. Sixty (n=60) subjects, who met the inclusion and exclusion criteria, were recruited and underwent MRI brain scanning using Philips 3-Tesla Achieva MR scanner as well as completed neuropsychological assessment using Wechsler Adult Intelligence Scale (WAIS-IV) (2008). The baseline MRI images were used to determine the presence of WMHs and scored using Fazekas scale. The neuropsychological testing included three index scales such as Perceptual Reasoning Index (PRI), Working Memory Index (WMI) and ProcessingSpeed Index (PSI). The analyses were carrying out by IBM SPSS Statistics version 22.0. Sixty subjects (n=18 males and n=42 females), aged between 25 to 62 years old were recruited. Approximately 30% of them had family history of heart attack, 10% on hypertension treatment and 60% without comorbidity. Among the subjects, 23 (38.3%) of them have WHMs on MRI, and the rest appeared normal. Among WMHs subjects, 39.1% were in younger age group (25-39) and 60.9% were in the middleage (40-62) group. The primary data suggested that the scores of neuropsychological test were variable among WMHs subjects, with brain region predilections. There was a significant association between subjects with and without WMHs in PRI, t (0.07,58)=0.07, p=0.02. Thus, age (r=0.3,p< 0.05) and QRISK scores (r=0.4, p<0.05) appeared to be correlated to the presence of WMHs. This result suggests that in older people, CSVD may contribute to cognitive decline by affecting information processing speed and executive function. Given that presence of WMHs may also indicate an increased risk of symptomatic cerebrovascular events, thus careful interpretation is required in order to determine its clinical relevance for the individual subjects.